2014
DOI: 10.1016/j.ihj.2014.10.411
|View full text |Cite
|
Sign up to set email alerts
|

Early and six-month assessment of bi-ventricular functions following surgical closure of atrial septal defect

Abstract: There was a significant improvement in RV systolic function and an insignificant change in RV and LV diastolic functions following surgical closure of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…In concordance with our results, Vijayvergiya et al [22] Also had revealed a significant reduction in RV systolic function following 6 months of surgical closure of ASD, by comparing results for S' wave, (17.75±3.5) cm\s in open ASD vs (11.55±4.9) cm\s at one-month post-surgery vs 11.60±3.4 cm/s at 6-month post-surgery (p<0.001).…”
Section: Discussionsupporting
confidence: 94%
“…In concordance with our results, Vijayvergiya et al [22] Also had revealed a significant reduction in RV systolic function following 6 months of surgical closure of ASD, by comparing results for S' wave, (17.75±3.5) cm\s in open ASD vs (11.55±4.9) cm\s at one-month post-surgery vs 11.60±3.4 cm/s at 6-month post-surgery (p<0.001).…”
Section: Discussionsupporting
confidence: 94%
“…Preoperative severe right ventricle dilatation and dysfunction significantly decreased in postoperative period and there was no significant change in LV ejection fraction in both groups. This is similar to other studies 24, 25…”
Section: Discussionsupporting
confidence: 93%
“…Vijayvergiya et al. found a significant improvement in RV systolic function following surgical closure of ASD …”
Section: Discussionmentioning
confidence: 99%